Annual Report 2003-04 - Planning Commission (Planning Commission, 2004)
The Planning Commission was constituted in March, 1950 by a Resolution of the Government of India, and it works under the overall guidance of the National Development Council. The Planning Commission consults the Central Ministries and the State Governments while formulating Five Year Plans and Annual Plans and also oversees their implementation. The Commission also functions as an advisory Planning body at the apex level.
Government of India Planning Commission Yojana Bhavan, New Delhi-110001
Government of India Planning Commission
Keywords: Role; Composition and Functions; Economy and the Plan: An Overview; The Plan; Major Activities in the Planning Commission; Agriculture Division; Backward Classes and Tribal Development Division Communication & Information Division; Development Policy Division; Education Division